'Novae, supernovae, or something else?' – (super-)nova highlights from Hoffmann & Vogt are quite certainly comets (ad 668 and 891). Issue 1 (4th November 2020) - Neuhäuser, Ralph; Neuhäuser, Dagmar L; Chapman, Jesse
ABSTRACT: Galactic novae and supernovae can be studied by utilizing historical observations, yielding explosion time, location on sky, etc. Recent publications by Hoffmann & Vogt present CVs (Cataclysmic Variables), supernova remnants, planetary nebulae, etc. as potential counterparts based on their list of historically reported transients from the Classical Chinese text corpus. Since their candidate selection neglects the state-of-the-art (e.g. Stephenson & Green), and since it includes 'broom stars' and 'fuzzy stars', i.e. probable comets, we investigate their catalogue in more detail. We discuss here their two highlights, the suggestion of two 'broom star' records dated ad 667 and 668 as one historical supernova and of the 'guest star' of ad 891 as recurrent nova U Sco. The proposed positional search areas are not justified due to translation and dating problems, source omission, as well as misunderstandings of historical Chinese astronomy and unfounded textual interpretations. All sources together provide strong evidence for comet sightings in both ad 668 and 891 – e.g. there are no arguments for stationarity. The ad 667 record is a misdated doublet of 668. Our critique pertains more generally to their whole catalogue of '24 most promising events': their speculations on counterparts lack a solid foundation and should not be used in follow-ups.